The Lion of the North: A Tale of the Times of Gustavus Adolphus - Henty, G. A. (George Alfred), 1832-1902 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Lion of the North: A Tale of the Times of Gustavus Adolphus" by G. A. Henty is a historical novel written during the late 19th century. This engaging tale focuses on the significant events of the Thirty Years' War, particularly highlighting the role of powerful figures like Gustavus Adolphus of Sweden and the experiences of Scottish soldiers who fought in his armies. Following the young protagonist, Malcolm Graheme, the narrative promises a blend of adventure, bravery, and exploration of pivotal moments in European history. At the start of the story, readers are introduced to a fierce spring storm in 1630 Scotland, where sixteen-year-old Malcolm waits anxiously by the Nith River for the arrival of two horsemen. Displaying remarkable courage, he swims across the torrential waters to guide Captain Hume and Colonel Munro to a safer crossing point. As the narrative unfolds, discussions between the characters reveal the political turmoil of the time and set the stage for Malcolm's impending journey to war in Germany, where he aspires to join the Swedish army and prove his valor. Through Malcolm's eyes, readers are given a glimpse into the human side of conflicts that shaped European history. (This is an automatically generated summary.)
Release date is 2004-02-01
Produced by Martin Robb, and David Widger
Keywords: Thirty Years' War, 1618-1648 -- Fiction; Gustav II Adolf, King of Sweden, 1594-1632 -- Fiction